2014
DOI: 10.1021/jm4016729
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Brain Penetrant 11β-Hydroxysteroid Dehydrogenase Type I Inhibitors and in Vivo Testing in Diet-Induced Obese Mice

Abstract: 11β-Hydroxysteroid dehydrogenase type 1 (11β-HSD1) has been widely considered by the pharmaceutical industry as a target to treat metabolic syndrome in type II diabetics. We hypothesized that central nervous system (CNS) penetration might be required to see efficacy. Starting from a previously reported pyrimidine compound, we removed hydrogen-bond donors to yield 3, which had modest CNS penetration. More significant progress was achieved by changing the core to give 40, which combines good potency and CNS pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 43 publications
(109 reference statements)
4
23
1
Order By: Relevance
“…These indicate that in the binding pocket there may be two hydrophobic regions that tolerate aromatic interactions, and in between these pockets, there was most likely a hydrogen-bonding partner. This feature arrangement is in line with the architecture of already crystallized 11β-HSD1 and 17β-HSD1, where inhibitors are anchored to the catalytically active amino acids by central hydrogen bonds and form further, adjacent hydrophobic contacts (e.g., the PDB structures 4c7j 70 and 3hb5 71 ).…”
Section: Resultssupporting
confidence: 78%
“…These indicate that in the binding pocket there may be two hydrophobic regions that tolerate aromatic interactions, and in between these pockets, there was most likely a hydrogen-bonding partner. This feature arrangement is in line with the architecture of already crystallized 11β-HSD1 and 17β-HSD1, where inhibitors are anchored to the catalytically active amino acids by central hydrogen bonds and form further, adjacent hydrophobic contacts (e.g., the PDB structures 4c7j 70 and 3hb5 71 ).…”
Section: Resultssupporting
confidence: 78%
“…: 4C7J) of human 11β-HSD1 co-crystallized with the 11β-HSD1 inhibitor 4-cyclopropyl- N -(trans-5-hydroxy-2-adamantyl)-2-(2-hydroxyethoxy)-thiazole-5-carboxamide (4YQ) 40 was used for all the docking experiments. 4YQ has a potent 11β-HSD1 IC 50 value of 9.9 nM and is structurally related to compound 4 of this study 42 . This enzyme and the co-crystallized ligand is therefore deemed appropriate to explore and predict the potential 11β-HSD1 inhibitory activity of compound 4 .…”
Section: Resultsmentioning
confidence: 75%
“…Failure was not due to the hypothesized effect of the inhibition of 11β-HSD1 on the regulation of the hypothalamic-pituitary-adrenal axis, with an overcompensation by the adrenal gland caused by the reduction in circulating cortisol [136], a phenomenon not clinically significant, but owing to a lack of sufficient efficacy on BW; data obtained in preclinical researches in animal models of obesity showed that, for the main part of the compounds, high doses of 11β-HSD1 inhibitors are requested for the control of glycemia and weight gain. It has been suggested that these high doses could be necessary for allowing these compounds to access the brain; however, mice with brain 11β-HSD1 KO mouse are indistinguishable from the control (WT) [137] and compounds designed to act on GC receptors present in the brain (receptors expressed in areas relevant to metabolic control), able to cross the blood-brain-barrier (BBB), showed negative results in DIO mice model of obesity [138]; thus, antiobesity activity as off-target effect of these compounds has been suggested. Table 6 reports the most recent compounds that were shown to affect BW, together with those that are currently in clinical trial.…”
Section: Review Costantino and Barloccomentioning
confidence: 99%